2021
DOI: 10.1080/1331677x.2021.1934509
|View full text |Cite
|
Sign up to set email alerts
|

Influence of COVID-induced fear on sovereign bond yield

Abstract: There is limited literature exploring the relationship between the sentiment of fear and bond markets. This study analyzes the influence of fear generated by the coronavirus on bond markets, particularly on the yield of sovereign bond debt issued by the G7 countries (Germany, Canada, the United States, France, Italy, Japan, and the United Kingdom). To accomplish this, search volumes compiled by Google Trends on the topic of coronavirus were used as a proxy for COVID-induced fear. The results from applying a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…This section presents a brief review of recent literature that examines the implication of COVID-19 associated uncertainty and fear on the global equity market. The inimitable effect of the COVID-19 pandemic outbreak on the global financial system can be cauterized as a decline in liquidity, increase in volatility, lower return, and cross-market or cross-asset economic shock spillover ( Al Guindy, 2021 , Baker et al, 2020 , Contessi and De Pace, 2021 , Huynh et al, 2021 , Paule-Vianez et al, 2021 , Rubbaniy et al, 2021 , Shaikh and Huynh, 2021 , Xu et al, 2021 , Zaremba et al, 2020 , Zhang et al, 2021 , among others). Although the empirical research question remains focused on COVID-19 and stock market behavior, the approach to measuring COVID-19's impact varies considerably.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This section presents a brief review of recent literature that examines the implication of COVID-19 associated uncertainty and fear on the global equity market. The inimitable effect of the COVID-19 pandemic outbreak on the global financial system can be cauterized as a decline in liquidity, increase in volatility, lower return, and cross-market or cross-asset economic shock spillover ( Al Guindy, 2021 , Baker et al, 2020 , Contessi and De Pace, 2021 , Huynh et al, 2021 , Paule-Vianez et al, 2021 , Rubbaniy et al, 2021 , Shaikh and Huynh, 2021 , Xu et al, 2021 , Zaremba et al, 2020 , Zhang et al, 2021 , among others). Although the empirical research question remains focused on COVID-19 and stock market behavior, the approach to measuring COVID-19's impact varies considerably.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Although the empirical research question remains focused on COVID-19 and stock market behavior, the approach to measuring COVID-19's impact varies considerably. For example, existing literature documents operationalization of Global COVID-19 fear index ( Al-Awadhi et al, 2020 , Mazumder and Saha, 2021 ; Salisu et al, 2020a; Salisu and Akanni, 2020 , Rubbaniy et al, 2021 , Zhang et al, 2021 ) measured from the daily death and confirmed cases, Feverish sentiment ( Huynh et al, 2021 ), pandemic anxiety indexes ( Yu et al, 2021 ), the COVID19+positive sentiment index ( Anastasiou et al, 2022 ), Equity Market Volatility Infectious Disease Tracker (EMV) ( Al Rababa'a et al, 2021 , Bai et al, 2021 , Baker et al, 2020 , Bouri et al, 2021 ; Salisu et al, 2020b), Pandemic intensity information search ( Goel and Dash, 2021 ), Coronavirus-related news (Biktimirov et al, 2020; Sun et al, 2021 ), COVID-19 Twitter intensity ( Al Guindy, 2021 ), investor attention or pandemic attention through GSVI ( Costola et al, 2021 , Smales, 2021 , Smales, 2020 , Tripathi and Pandey, 2021 , Xu et al, 2021 ), and pandemic-induced fear sentiment or pandemic uncertainty ( Chen et al, 2020 , Chundakkadan and Nedumparambil, 2021 , Liu et al, 2021 , Lyócsa et al, 2020 , Paule-Vianez et al, 2021 , Su et al, 2021 , Subramaniam and Chakraborty, 2021 , Szczygielski et al, 2022 ; Vasileiou, 2021). Table 1 presents a brief overview of recent literature and its findings.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…This phenomenon can be explained by the COVID impact on sovereign bonds and sovereign risk. For instance, ( Paule-Vianez, Orden-Cruz, & Escamilla-Solano, 2021 ) analyse the influence of fear generated by the coronavirus on various bond markets and show its significant impact on the yields, including the US bonds. The authors demonstrate that a one-point increase in COVID-induced fear was associated with an increase in the weekly change in the sovereign bond yield of around 0.0007% (see also Andrieş, Ongena, & Sprincean, 2021 for the analysis of the reaction of the whole yield curve).…”
Section: The Datamentioning
confidence: 99%
“…Paule‐Vianez et al (2022) analysed the influence of COVID‐induced fear on the sovereign bond yield of the G7 countries using search volumes compiled by Google Trends on the topic of coronavirus as a proxy for COVID‐induced fear. The results from applying a panel data approach from 1 January 2020 to 30 December 2020 showed that this fear positively impacted the 10‐year sovereign bond yield.…”
Section: Review Of the Literaturementioning
confidence: 99%